If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-36-7x=8x-12+3x
We move all terms to the left:
6x-36-7x-(8x-12+3x)=0
We add all the numbers together, and all the variables
6x-7x-(11x-12)-36=0
We add all the numbers together, and all the variables
-1x-(11x-12)-36=0
We get rid of parentheses
-1x-11x+12-36=0
We add all the numbers together, and all the variables
-12x-24=0
We move all terms containing x to the left, all other terms to the right
-12x=24
x=24/-12
x=-2
| 4x+42+12x=3x-10 | | 6x-36-7x=8x-12+3x/ | | -6y+4=6-y | | p−16+4=4(2−p) | | 3x+4+5x=12 | | -0.25x+1.3=-0.55x-0.2* | | (13x+5)+(8x-14)=180 | | -3(x+2)+5x=-14 | | x6+5=13 | | 3x+7x-4=2(5x+4) | | 6(r+1)=-2(1-2r)-6 | | 3.5d+9.75=5.25d | | n/3+2/3=-n+3 | | -6(8+6x)=-192 | | 8x+27x-10=7(5x+8) | | -14x-10=4 | | 3x+9=4–5x | | x–5=-2 | | 5x+15x-8=5(4x+3) | | Z(x+4)=-3(x+5) | | 11x8=11x+8 | | -3.5z=14 | | 5y^2=-30y | | (2x-27)+x=180 | | 10/x+5=11 | | 2/3(9w-24)=-10 | | 12z2=34z−12 | | (x+40)=(3x-20)=180 | | 3x=-3-9 | | |5x|-10=20 | | 11=b+7 | | 15.847=2x(102/149) |